Case Report: Complete Necrosis of a Large Adrenocortical Cancer and Liver Metastases Achieved by Selective Arterial Embolization: A Case Study and Review of Literature - Huszty, Gergely; Doros, Attila; Farkas, Katalin; Kóbori, László; Reismann, Péter; Tőke, Judit; Tóth, Miklós; Igaz, Peter (Frontiers in Endocrinology, 2021)
There is very limited experience regarding the interventional radiological treatment of adrenocortical cancer (ACC). We present the case of a 57 year-old patient with a large, potentially unresectable left-sided ACC and two hepatic metastases. Both liver tumors were effectively treated by trans-arterial embolization (TAE), followed by TAE of the bulky primary tumor as a life-saving intervention necessitated by severe intratumoral bleeding. Surgical removal of the primary tumor revealed complete necrosis. The patient is considered tumor free after 3.5 years. To the best of our knowledge, this is the first example to show that even a primary ACC may be completely ablated by selective embolization, and the fourth to prove the curative potential of liver TAE for ACC metastases. This case highlights the potential of selective embolization in ACC treatment.